2020
DOI: 10.1017/s0021859620000362
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of the main risk periods of Botrytis cinerea infection on grapevine based on phenology, weather conditions and airborne conidia

Abstract: In the present study, a new method for a decision-support system for fungicide administration against the pathogen Botrytis cinerea in vineyards was developed based on Integrated Pest Management principles which identified an infection risk before the appearance of disease symptoms. The proposed method is based on the combination of (i) the phenological observations of the main susceptible stages to infection, (ii) the airborne spores monitoring, (iii) the forecasting of the suitable meteorological conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…We also found a strong correlation with relative humidity of the same day. This period of three to four days agrees with the indicated period by González-Fernández et al [16], who found a period between four to six days (depending on the phenological stage under propitious meteorological conditions) for conidia germination and plant infection since the detection of conidia presence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also found a strong correlation with relative humidity of the same day. This period of three to four days agrees with the indicated period by González-Fernández et al [16], who found a period between four to six days (depending on the phenological stage under propitious meteorological conditions) for conidia germination and plant infection since the detection of conidia presence.…”
Section: Discussionsupporting
confidence: 90%
“…According to this, we considered the flowering (S6-BBCH scale) as one of the most vulnerable grapevine phenological stages to B. cinerea infection. For the Ribeiro PDO vineyard area, González-Fernández et al [16] previously found that the highest airborne conidia levels are usually recorded near to the flowering phenological stage, thus indicating a higher activity and fungal development in this period. The bioclimatic indicator developed for this pathogen based on the Magarey model, gave as a result that the flowering stage is one of the most susceptible stages to infection [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As a consequence, a reduction of the phytopathological fungal pressure in the vineyard could occur due to the less frequent propitious humidity conditions expected for infection and disease development, mainly in the Rias Baixas DO of the Eurosiberian area and the nearest transition zones. Therefore, a significant reduction in the number of phytochemical treatments will be expected, which will diminish the production costs and the risk of environmental pollution [106][107][108]. Malheiro et al [31] noted that the downy mildew contamination risk is low for BBLI values below 2500 and high for values exceeding 5100 [102].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification and quantification of the spore load in the atmosphere as bioindicators of pathogen presence, and their relationship with the meteorological and geographical data allows us to prevent the frequency and severity of diseases early [58]. Several studies detected a high degree of association between the aerial conidia concentration and the lesion density of the plants one week later, which shows the relation of disease development with spore concentrations in the atmosphere of the crop during previous periods [59][60][61]. The learning of the different ecological processes behavior of phytopathogenic fungus in the atmosphere of the crop is very important in regions where the cultivated area tend to the increase before the pressure of disease could be high.…”
Section: Discussionmentioning
confidence: 99%